Penerapan Metode PBL Berbantuan Video Meningkatkan Gotong - Royong Fase B Kelas IV SDN Nanga Bulik 4 Lamandau - Marietha Hunyaang; Hartutik Hartutik (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
The problem found in grade IV Phase B of SDN Nanga Bulik 4 is the low aspect of the dimension of mutual cooperation and the target learning achievement of students. This is influenced by the character of students who tend to be individualistic, lack of awareness, the influence of social media and technology. Another causative factor from the teacher is that they have not used student-centered learning methods and encourage active involvement of students in the learning process. To overcome this challenge, interesting learning methods are needed in order to improve the aspects of mutual cooperation and student learning achievement. One of the methods that has proven effective is the application of the video-assisted Problem Based Learning (PBL) method. The purpose of this research is to improve the character of the dimension of mutual cooperation and the target learning outcomes of students by applying the PBL model assisted by video media, the material Experiencing God's Commandments in Shared Life, grade IV Phase B of SDN Nanga Bulik 4. The focus of this research is on the dimension of mutual cooperation, from the profile of Pancasila students with the aim of improving the affective aspect in the learning process. The method used in this study is classroom action research in 2 cycles with 4 stages, namely planning, implementation, evaluation, and reflection, with a total of 5 respondents. The results of the research cycle I to cycle II of the gotong royong aspect showed an average increase from 25% to 50%. Furthermore, the results of the research cycle I to cycle II of the cognitive aspect showed an increase from 67 to 85.6. The results of the reflection recommend that there needs to be assistance in the affective aspect so that it can improve the character of mutual cooperation of the Pancasila (P3) student profile and the cognitive aspect of students. The implications of these findings confirm that the application of the video-assisted PBL method can improve the character of mutual cooperation and student learning achievements.